2003
DOI: 10.1128/mcb.23.22.7947-7956.2003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Fat Mass in Mice Lacking Orphan Nuclear Receptor Estrogen-Related Receptor α

Abstract: The estrogen-related receptor ␣ (ERR␣) is an orphan member of the superfamily of nuclear hormone receptors expressed in tissues that preferentially metabolize fatty acids. Despite the molecular characterization of ERR␣ and identification of target genes, determination of its physiological function has been hampered by the lack of a natural ligand. To further understand the in vivo function of ERR␣, we generated and analyzed Estrra-null (ERR␣ ؊/؊ ) mutant mice. Here we show that ERR␣ ؊/؊ mice are viable, fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
327
4
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(341 citation statements)
references
References 75 publications
9
327
4
1
Order By: Relevance
“…Cumulative evidences indicate that another ERR subtype, ERRa, plays significant roles in energy metabolism and mitochondrial biogenesis in certain target cells and tissues via direct regulation of genes involved in fatty acid oxidation, ERRb suppresses prostate cancer cell growth S Yu et al glucose metabolism, oxidative phosphorylation and mitochondrial fusion Huss et al, 2004;Schreiber et al, 2004;Wende et al, 2005;Soriano et al, 2006;Villena et al, 2007). Moreover, ectopic ERRa expression can promote lipid accumulation in primary cardiac myocytes (Huss et al, 2004), whereas its loss of function reduces body fat in ERRa-knockout mouse (Luo et al, 2003). In a recent expression profiling study of all 49 NRs in mouse tissues, ERRb is shown to be widely and rhythmically expressed in many organ systems, suggesting that ERRb together with other NRs are important in maintaining global basal metabolism under circadian control Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative evidences indicate that another ERR subtype, ERRa, plays significant roles in energy metabolism and mitochondrial biogenesis in certain target cells and tissues via direct regulation of genes involved in fatty acid oxidation, ERRb suppresses prostate cancer cell growth S Yu et al glucose metabolism, oxidative phosphorylation and mitochondrial fusion Huss et al, 2004;Schreiber et al, 2004;Wende et al, 2005;Soriano et al, 2006;Villena et al, 2007). Moreover, ectopic ERRa expression can promote lipid accumulation in primary cardiac myocytes (Huss et al, 2004), whereas its loss of function reduces body fat in ERRa-knockout mouse (Luo et al, 2003). In a recent expression profiling study of all 49 NRs in mouse tissues, ERRb is shown to be widely and rhythmically expressed in many organ systems, suggesting that ERRb together with other NRs are important in maintaining global basal metabolism under circadian control Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The phenotype of the esrra KO mouse also indicates that ERRa is involved in energy metabolism. 9 Similarly, the obese phenotype observed in the esra KO mouse argues that ERRa by crossreaction with EREs might play an important role in energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The phenotype of the esrra KO mouse also indicates that ERRa is involved in energy metabolism. 9 Similarly, the obese phenotype observed in the esra KO mouse argues that ERRa by crossreaction with EREs might play an important role in energy metabolism. 18 A recent study by Laflamme et al 17 provided evidence that the long repeats of ESSRA23 are associated with a higher lumbar spine bone mineral density, indicating cross-regulation by ERRa and ERa of phenotypes in addition to those of energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of ERRs appears to be constitutive, with the ligand binding pocket stably arranged in an active conformation without ligand (Xie et al 1999;Greschik et al 2002;Greschik et al 2004). Because ERRα is widely expressed in adult tissues, especially in tissues that utilize or can utilize fatty acid β-oxidation, many studies have addressed its role in cellular energetics (Luo et al 2003). Loss of ERRβ results in placental defects and mid-gestational death of embryos, despite relatively limited expression in adult (Luo et al 1997).…”
Section: Errsmentioning
confidence: 99%